Doctor-Patient Communication: Speed Bumps and Hiccups - Jane Goleman (Association of American Medical Colleges, 2010)
Abstract Introduction This resource is a PowerPoint presentation designed for use in interactive small-group discussions of cross-cultural communication. It can be used with first- to third-year medical students. The goal is to review good communication skills as well as the guidelines for working with an interpreter. It also introduces Kleinman's questions for eliciting the patient's perspective. There are three short video clips of a doctor-patient encounter between a Caucasian physician and a Somali family. Methods Although doctor-patient communication and diversity sessions may not be valued by the students as highly as their basic science lectures, these sessions are the foundation of clinical practice. The relationship between the physician, the patient, and their family is crucial to obtaining an accurate and complete history, which leads to the correct diagnosis. The relationship is also crucial in leveraging change in patient behavior and adherence. Unfortunately, when the first- and second-year students begin assisting with patient care in their third- and fourth-years, they will realize how poorly some physicians communicate under the time constraints and pressures of a busy practice. Results This resource was used with first-year medical students in clinical assessment and problem solving (CAPS), which is taught in physician-facilitated small groups of 12 students. Eleven facilitators evaluated the session. Of them, four strongly agreed that the session encouraged discussion on the importance of gaining the patient's perspective, five agreed, and two were neutral. Some students felt that no physician would behave as the physician in the first video clip, and others believed the traditional illness was far-fetched (although the scenario came directly from my practice). Despite these perspectives, the students enjoyed the videos because they were entertaining and made a memorable point. Discussion The videos were originally created and presented within a lecture format to the entire medical staff as they were required to attend diversity training. The physicians were pleasantly surprised and engaged during the entire presentation and there was much discussion afterwards.